CODE-SWITCHING PRACTICES IN ENGLISH LANGUAGE PEDAGOGY: CLARITY ENHANCEMENT IN INDONESIAN EFL EDUCATION - Nasution, Rafif Akmal Fawwaz; Hidayat, Raditiya Taufik Nur; Pramesti, Rahma Putri; Yuliani, Zuma Adella (ISLLAC : Journal of Intensive Studies on Language, Literature, Art, and Culture, 2024)
This study investigates the impact of code-switching on communication clarity in an EFL classroom in Indonesia. Data were collected through one classroom observation and interviews with one teacher and three students at a senior high school in Surakarta. Results indicate that code-switching significantly enhances communication clarity, boosting students' confidence and interest in the EFL classroom. The finding highlights the necessity for EFL teachers to incorporate code-switching strategies for effective communication and language learning activity.